From metaphysical representations to aesthetic life : toward the encounter with the other in the perspective of Daoism - Lacertosa, Massimiliano, 1980- (Albany : State University of New York Press, 2023)
Reevaluates Western and Chinese philosophical traditions to question the boundaries of entrenched conceptual frameworks.
Preface -- Acknowledgements -- Note on the text -- Introduction -- 1. Toward the encounter with the other -- 2. From worldview to metaphor -- 3. From metaphor to ethics -- 4. From ethics to Ziran -- 5. From Ziran to aesthetics -- Returning to the beginning (by way of conclusion) -- Notes -- References -- Index.
Includes bibliographical references and index
Description based on online resource; title from PDF title page (ProQuest Ebook Central, viewed on August 03, 2023).
eBooks on EBSCOhost
Keywords: Taoist philosophy; Philosophy, Chinese; Aesthetics; Philosophie taoïste.; Philosophie chinoise; PHILOSOPHY / Taoist; Aesthetics; Philosophy, Chinese; Taoist philosophy